2009
DOI: 10.1111/j.1476-5381.2009.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indomethacin‐loaded nanocapsules in experimental models of inflammation in rats

Abstract: Background and purpose:The effects of systemic treatment with indomethacin-loaded nanocapsules (IndOH-NC) were compared with those of free indomethacin (IndOH) in rat models of acute and chronic oedema. Experimental approach: The following models of inflammation were employed: carrageenan-induced acute oedema (measured between 30 min and 4 h), sub-chronic oedema induced by complete Freund's adjuvant (CFA) (determined between 2 h and 72 h), and CFA-induced arthritis (oedema measured between 14 and 21 days). Key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 33 publications
6
64
0
Order By: Relevance
“…This method of drug delivery has been shown to decrease gastrointestinal side effects and increase the brain biodistribution of IndOH. 19,46 In the present study, we reported that by using LNCs, even low concentrations of IndOH (such as 50 µM) were able to protect against cell death induced by Aβ1-42 exposure in organotypic culture. Possible mechanisms underlying the similar effects observed with both concentrations of IndOH-LNCs in the present study may include the NC uptake endocytosis by the cells achieved through endocytosis.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This method of drug delivery has been shown to decrease gastrointestinal side effects and increase the brain biodistribution of IndOH. 19,46 In the present study, we reported that by using LNCs, even low concentrations of IndOH (such as 50 µM) were able to protect against cell death induced by Aβ1-42 exposure in organotypic culture. Possible mechanisms underlying the similar effects observed with both concentrations of IndOH-LNCs in the present study may include the NC uptake endocytosis by the cells achieved through endocytosis.…”
Section: Discussionmentioning
confidence: 79%
“…Our previous work has shown that this formulation increased the levels of IL-10 in peripheral inflammation models. 46 Here, we noticed that treatment with IndOH-LNCs increased levels of IL-10 in the presence or absence of Aβ. In this way, our data demonstrate that IndOH was able to break the inflammatory response induced by Aβ, culminating in the protective effect on cell death, as observed by PI incorporation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nanocapsules containing compound 1 were prepared by the SD previously described method (Bernardi et al, 2009;Zili et al, 2005), as described in Table 1 (formulations VII-VIII). Concisely, an acetonic solution of PLGA containing or not the lipophilic surfactant Span ® 80 was prepared.…”
Section: Preparation Of Nanocapsulesmentioning
confidence: 99%
“…The capacity of the LNC to increase the drug's action on the reduction of proinflammatory cytokines has also been demonstrated in a rat arthritis model, in which LNC that contained indomethacin (IndOH-LNC) reduced cytokines; however, there was no significant effect for the drug in solution. 43 Finally, resistance to MTX is another current issue in the treatment of RA because it compromises clinical responsiveness to the drug. Resistance to MTX occurs because of a wide range of mechanisms, including MTX uptake by a reduced folate carrier, an increase of MTX efflux, a decrease of MTX polyglutamation, and an overexpression of dihydrofolate reductase.…”
mentioning
confidence: 99%